Grey Matters: Charting the Development of the Shadow Economy - Donal MacGéidigh; Friedrich Schneider; Matthias Blum (Center for Economic Studies and ifo Institute (CESifo), 2016)
The shadow economy has long been an area of research for policymakers. The determinants of underground activity of late have been identified as high tax burdens and increased regulation, but has this relationship always existed? This seminal work examines the shadow economy in Norway, Sweden, the United Kingdom and the United States over the past 145 (from 1870 to 2015) years using the Currency Demand Approach and finds that the underground economy is stabilising. To our knowledge this is the first attempt to estimate the size and development of the shadow economy over such a long period and due to this we get some new insights. Our results clearly show that the shadow economy in earlier times was considerably higher than in the last 50 years. This paper also analyses whether a plateau has been reached and questions what efforts could be made to further reduce this informal economy.
Keywords: H26; K42; O17; 330; shadow economy; underground activity; historical tax rates